(untitled) (Nigerian Journal of Technology, 2013)
Despite the cultural differences between university and industry, the mutual benefits from collaboration between university and industry have long been recognized in the advanced countries. Recently, the issue of technology transfer and collaboration between universities and industries has been receiving attention in the developing countries. A survey was recently conducted in order to determine the issue of technology transfer between schools of engineering and sciences in universities and industries within the north central, south south and western region of Nigeria. The survey was conducted by asking appropriate persons to respond to a set of questions and having interviews with them. The survey revealed that there is a very low level of technology transfer and collaboration between most industries and universities in this region. The reasons for this state of affairs are highlighted and suggestions are made to effectively increase the level of technology transfer and collaboration in Nigeria.